generated from UofSC-Fall-2022-Math-300-H01/homework2
-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathmain.tex
73 lines (62 loc) · 2.1 KB
/
main.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
\documentclass[12pt]{amsart}
\usepackage{amsmath}
\usepackage{amsthm}
\usepackage{amsfonts}
\usepackage{amssymb}
\usepackage{ebproof}
\usepackage[margin=1in]{geometry}
\usepackage{hyperref}
\hypersetup{
colorlinks=true,
linkcolor=blue
}
\theoremstyle{definition}
\newtheorem{theorem}{Theorem}[section]
\newtheorem{lemma}[theorem]{Lemma}
\newtheorem{definition}[theorem]{Definition}
\newtheorem{corollary}[theorem]{Corollary}
\newtheorem{proposition}[theorem]{Proposition}
\newtheorem{conjecture}[theorem]{Conjecture}
\newtheorem{remark}[theorem]{Remark}
\newtheorem{example}[theorem]{Example}
\newtheorem{problem}[theorem]{Problem}
\newtheorem{notation}[theorem]{Notation}
\newtheorem{question}[theorem]{Question}
\newtheorem{caution}[theorem]{Caution}
\begin{document}
\title{Homework 3}
\maketitle
\begin{enumerate}
\item Give natural deduction proof of the formula
\begin{displaymath}
(A \leftrightarrow B) \leftrightarrow (A \to B) \land (\neg A \to \neg B)
\end{displaymath}
\item Show that $(A \to B) \to (B \to A)$ cannot be proven. Given example statements
for $A$ and $B$ where $A \to B$ is true but $B \to A$ is not. Can you make
them mathematical statements?
\item A formula is in \textit{conjunctive normal form} if it is written as
\begin{displaymath}
X_1 \land X_2 \land \cdots \land X_n
\end{displaymath}
where each
\begin{displaymath}
X_i = Y^1_i \lor \cdots \lor Y^j_i
\end{displaymath}
and each $Y^l_i$ is either $\neg A$ or $A$ for some propositional variable $A$.
Which of the following are in conjunctive normal form:
\begin{itemize}
\item $$ \neg (A \lor B) $$
\item $$ \neg A \land (B \lor C)$$
\item $$ \neg A \lor \neg B \land C$$
\item $$ (A \land B) \lor C$$
\end{itemize}
\item It is a fact that any formula in propositional logic can be rewritten in
conjunctive normal form up to bi-implication. Rewrite the following formula
in conjunctive normal form up to bi-implication.
\begin{itemize}
\item $$A \land (B \lor (C \land D))$$
\item $$\neg (A \land (B \lor C))$$
\item $$(A \to B) \lor C$$
\end{itemize}
\end{enumerate}
\end{document}